-2(-2x+3)+4x=-2(6+3x)+3x

Simple and best practice solution for -2(-2x+3)+4x=-2(6+3x)+3x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -2(-2x+3)+4x=-2(6+3x)+3x equation:



-2(-2x+3)+4x=-2(6+3x)+3x
We move all terms to the left:
-2(-2x+3)+4x-(-2(6+3x)+3x)=0
We add all the numbers together, and all the variables
-2(-2x+3)+4x-(-2(3x+6)+3x)=0
We add all the numbers together, and all the variables
4x-2(-2x+3)-(-2(3x+6)+3x)=0
We multiply parentheses
4x+4x-(-2(3x+6)+3x)-6=0
We calculate terms in parentheses: -(-2(3x+6)+3x), so:
-2(3x+6)+3x
We add all the numbers together, and all the variables
3x-2(3x+6)
We multiply parentheses
3x-6x-12
We add all the numbers together, and all the variables
-3x-12
Back to the equation:
-(-3x-12)
We add all the numbers together, and all the variables
8x-(-3x-12)-6=0
We get rid of parentheses
8x+3x+12-6=0
We add all the numbers together, and all the variables
11x+6=0
We move all terms containing x to the left, all other terms to the right
11x=-6
x=-6/11
x=-6/11

See similar equations:

| (x+8)^4=16. | | x/8-4=24 | | 7z-z=-1+4z-1-4 | | 6+2r=-4 | | 16-5(3d-4)=8(-2d+11) | | v/5+4.2=-8.3 | | Y=4*1.25^x | | 45=10-5a | | 3z+2-z=4+z+8 | | 2/3m-8=2/3 | | 1/5x-12=2 | | F(x)=47(1.25)x-1 | | 2y=10y+3y | | 2x+1+5x*2x-1=36 | | 5y+y=5y-2 | | 8x^+6x=5 | | 2x^2+62=0 | | 1/x+1/12-x=3/8 | | F(20)=4x+12 | | -9=3+t | | 9r+15=-12 | | 37.5+x=50 | | 7×=4x+27 | | u+3.9=9.85 | | x+12=–15 | | 2d=2,4 | | a+12.5=10.1 | | 2y+10y+3y=y | | 35.3=d-(-3.81) | | y-1.7=2.89 | | 8x9=x | | 3/4q=1/3 |

Equations solver categories